#TITLE_ALTERNATIVE# - FERY SANTOSA (NIM : 10106013); Pembimbing Tugas Akhir : Dr. Sutawanir Darwis
In a reservoir area, there are differences in value-pameter parameters that affect the condition of the reservoir. Composite Reservoir is a reservoir which has two or more reservoir area based on different parameter values of permeability. There are three cases which have given to this composite reservoir that is for infinite, constant pressure outer boundary,and closed outer boundary homogeneous reservoirs. One of the characteristic parameters that will explain that the rate of mobility through two pieces of the regression equation. This final project will explain the condition of the two regions of composite reservoir for the case in the infinite outer boundary of flow rate decline analysis, especially for the well and the radius of the discontinuity. And it also explain the equation used to describe the condition of the composite reservoir through one of partial differential equations by using the equation of radial diffusivity.